Analysing the performance of farmers in the mango value chain in major production areas in Davao Region, Philippines - Aguinaldo, R.; Sarmiento, Jon; Digal, L.; Balgos, C.; Castillo, A. (Australian Centre for International Agricultural Research, 2013)
The Philippine ‘Carabao’ mango has established its reputation locally and internationally as a superior breed among other varieties in the world but its supply pales in comparison with the local and international demand. The Philippine mango industry is also facing a complex market structure brought by different actors in the supply chain. Hence, this study was conducted to analyse the performance of farmers in the value chain of mango in three major producing areas in the Davao region: Davao City; Digos City in Davao del Sur; and the Island Garden City of Samal in Davao del Norte. Specifically, the study aims to identify the roles of different actors in the mango supply chain, assess the profitability of the actors and identify the factors affecting profitability. Value chain and net margin analyses were employed. The results reveal that the interrelatedness of farmers, financiers and middlemen has a primary effect on the distribution of benefits among the actors in the mango supply chain. Statistical analysis suggests that trained farmers in Digos City who have trees of mature age and who are not under financing arrangement are more profitable. Econometric analysis identified volume sold and prices as drivers of profitability, while land area and cost of production negatively influenced profitability. It also confirms that non-financed farmers are more profitable than financed farmers. Wholesaling activities are favoured in Digos City due to minimal marketing costs, while retailing activities are best in Davao City due to larger captive market, specifically the Bankerohan public market.